Following Jesus in turbulent times : disciple-making in the Arab world - Kashouh, Hikmat (Langham Creative Projects, 2018)
Using his church's powerful testimony, Pastor Hikmat Kashouh teaches us how to disciple refugees from Arab contexts. Jesus is drawing more and more people to himself in the Middle East through the ministry of churches like Resurrection Church in Lebanon, and through miraculous divine visitations of God. In this book the church has a resource to help love, serve and disciple refugees, equip emerging indigenous leaders and understand discipleship of people from non-Christian backgrounds.